STUDY ON THE IRON COMPLEXES OF EXPANDED PORPHYRINS, PHTHALOCYANINES, AND PORPHYRAZINES - Bir Prakash Mishra; Jai Ram Singh (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2015)
Iron porphyrin complexes, which have the same core structure as the heme cofactor, are perhaps the most widely used compounds in O2 binding and activation studies. Early efforts were made in stabilizing an Fe–O2 moiety as a functional mimic of O2-bound hemoglobin and myoglobin, to gain structural and electronic insights into the nature of the Fe–O2 bonding in these heme proteins. As early as 1936, Pauling and Coryell determined that the Fe–O2 group in oxyhemoglobin was diamagnetic. This led to the proposal of several models to describe the nature of Fe–O2 bonding ,which are detailed in several reviews.